Pharmacomodulation of the antimalarial plasmodione: synthesis of Biaryl- and N-Arylalkylamine analogues, antimalarial activities and physicochemical properties - Urgin, Karène; Ehrhardt, Katharina; Lanzer, Michael (Molecules, 2017)
With the aim of increasing the structural diversity on the early antimalarial drug plasmodione, an efficient and versatile procedure to prepare a series of biaryl- and N-arylalkylamines as plasmodione analogues is described. Using the naturally occurring and commercially available menadione as starting material, a 2-step sequence using a Kochi-Anderson reaction and subsequent Pd-catalyzed Suzuki-Miyaura coupling was developed to prepare three representative biphenyl derivatives in good yields for antimalarial evaluation. In addition, synthetic methodologies to afford 3-benzylmenadione derivatives bearing a terminal -N(Me)2 or -N(Et)2 in different positions (ortho, meta and para) on the aryl ring of the benzylic chain of plasmodione were investigated through reductive amination was used as the optimal route to prepare these protonable N-arylalkylamine privileged scaffolds. The antimalarial activities were evaluated and discussed in light of their physicochemical properties. Among the newly synthesized compounds, the para-position of the substituent remains the most favourable position on the benzyl chain and the carbamate -NHBoc was found active both in vitro (42 nM versus 29 nM for plasmodione) and in vivo in Plasmodium berghei-infected mice. The measured acido-basic features of these new molecules support the cytosol-food vacuole shuttling properties of non-protonable plasmodione derivatives essential for redox-cycling. These findings may be useful in antimalarial drug optimization.